2022
DOI: 10.1021/acs.inorgchem.2c00909
|View full text |Cite
|
Sign up to set email alerts
|

Buffer Assists Electrocatalytic Nitrite Reduction by a Cobalt Macrocycle Complex

Abstract: This work reports a combined experimental and computational study of the activation of an otherwise catalytically inactive cobalt complex, [Co(TIM)-Br 2 ] + , for aqueous nitrite reduction. The presence of phosphate buffer leads to efficient electrocatalysis, with rapid reduction to ammonium occurring close to the thermodynamic potential and with high Faradaic efficiency. At neutral pH, increasing buffer concentrations increase catalytic current while simultaneously decreasing overpotential, although high conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
(116 reference statements)
0
15
0
Order By: Relevance
“…Moreover, recent studies on electrocatalytic nitrite reduction using metals other than copper have addressed the important role of the buffer during catalysis. The group of Smith and co-workers has reported that phosphate buffer assists in the aqueous electrocatalytic reduction of nitrite, making their cobalt-based complex active for the reduction of nitrite . Likewise, the group of Bren and co-workers reported an iron-based complex for the reduction of nitrite to hydroxylamine and ammonium that is only active in the presence of buffer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies on electrocatalytic nitrite reduction using metals other than copper have addressed the important role of the buffer during catalysis. The group of Smith and co-workers has reported that phosphate buffer assists in the aqueous electrocatalytic reduction of nitrite, making their cobalt-based complex active for the reduction of nitrite . Likewise, the group of Bren and co-workers reported an iron-based complex for the reduction of nitrite to hydroxylamine and ammonium that is only active in the presence of buffer …”
Section: Introductionmentioning
confidence: 99%
“…The group of Smith and coworkers has reported that phosphate buffer assists in the aqueous electrocatalytic reduction of nitrite, making their cobalt-based complex active for the reduction of nitrite. 54 Likewise, the group of Bren and co-workers reported an ironbased complex for the reduction of nitrite to hydroxylamine and ammonium that is only active in the presence of buffer. 55 Following this, we report here for the first time a detailed and complete catalytic cycle of the electrocatalytic nitrite reduction mechanism in aqueous solution by a bio-inspired CuNiR catalyst, Cu(tmpa), and pinpoint important reaction parameters for the development and electrochemical analysis of new bio-inspired CuNiR species and other catalytic sites for the nitrite reduction reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[30][31][32][33] Since cobalt demonstrates the optimum NO 2 À binding and N-O bond dissociation thermodynamics in the catalytic volcano plot, 34,35 Co-based heterogeneous nanomaterials, including metallic Co, 36 oxides, 37,38 borides 39 and phosphides 40 with diverse structures and morphologies, attain attractive eNO x À RR current densities, but the unclear atomic active sites and uncontrollable secondsphere structures hamper rational catalyst development and optimization. On the other hand, eNO x À RR can be catalysed by homogeneous, macrocyclic Co complexes, [41][42][43][44][45][46] but realizing complete and high-yield NO 2 À to NH 4 + transformation is particularly challenging under mild potentials, due to the inefficiency of consecutive 6e À transfer to the catalytic centre. 47 In this situation, we speculate that cobaloximes with a CoN 4 skeleton should be an ideal platform for 6e À /8H + NO 2 À to NH 4 + reduction (Fig.…”
mentioning
confidence: 99%
“…Minimal work has been done on H + -induced catalytic NO (g) generation from metal-NO 2 − species; however, there are a few reports on electrocatalytic NO formation from metal-NO 2 − . 24,28 Being a very important biological molecule ( vide supra ), developing a catalyst for selective NO (g) formation via H + -induced NO 2 − transformation is highly necessary to treating several biological dysfunctions. In the last few years, we have successfully developed a few models for NO 2 − reduction to NO on cobalt and iron centers, demonstrating metal-nitrosyls formation.…”
mentioning
confidence: 99%